Some questions about the “duty” category in labour law - Zhumabayeva А.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2021)
Responsibility is an essential element of the development and functioning of society and human beings as an integral part of society. Therefore, a comprehensive scientific study of the category «duty» is of particular importance in the study of the fundamental rights and freedoms of the individual. The article discusses the various approaches of representatives of different branches of law to the definition of the concept of duty as a legal category, its essence and content. The multiplicity of theoretical views on the study of this category of law is usually reduced to two understandings of the definition of duty through a measure of due conduct and a measure of necessity. It is important to note that traditionally the category of duty was considered and studied by researchers, together with a theoretical and practical analysis of human rights and freedoms. «Duty» as a category of labour law has its own distinctive characteristics and characteristics.